2011
DOI: 10.1111/j.1365-3083.2011.02608.x
|View full text |Cite
|
Sign up to set email alerts
|

A Variant of the Il2ra / Cd25 Gene Predisposing to Graves’ Disease is Associated with Increased Levels of Soluble Interleukin‐2 Receptor

Abstract: Alpha‐subunit of the IL‐2 receptor (IL‐2Rα) encoded by the IL2RA/CD25 gene binds IL‐2 that plays a pivotal role in the regulation of T cell function. Levels of a soluble form of IL‐2Rα (sIL‐2Rα) lacking the transmembrane and cytoplasmic domains were shown to be increased in several autoimmune diseases including Graves’ disease (GD). Recent studies showed association between the IL2RA/CD25 gene variants and several autoimmune diseases including GD. In this study, we analyzed whether polymorphic markers rs210428… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
1
27
1
1
Order By: Relevance
“…This receptor regulates lymphocytes through controlling T reg activity [33]. This gene could be considered as a general autoimmunity gene whose variants showed association with susceptibility to numerous autoimmune diseases especially T1D [33,34,7,25,11] and Grave's disease [35]. It was also shown that rs rs2104286 of IL2RA gene variants was correlated with decreased serum level of S-IL2RA in healthy subjects and patients affected with T1D and Multiple Sclerosis [36].…”
Section: Discussionmentioning
confidence: 96%
“…This receptor regulates lymphocytes through controlling T reg activity [33]. This gene could be considered as a general autoimmunity gene whose variants showed association with susceptibility to numerous autoimmune diseases especially T1D [33,34,7,25,11] and Grave's disease [35]. It was also shown that rs rs2104286 of IL2RA gene variants was correlated with decreased serum level of S-IL2RA in healthy subjects and patients affected with T1D and Multiple Sclerosis [36].…”
Section: Discussionmentioning
confidence: 96%
“…About 25-50 % of GD patients have clinical signs of Graves' ophthalmopathy (GO), most having mild disease [2,3]. Genome-wide screens conducted in GD have identified a number of putative susceptibility genes in GD [4] and several gene loci have been reported to be associated with a risk of developing GD, including HLA [4,5], CTLA4 [6], PTPN22 [7], CD40 [8], IL2RA [9], IL21 [10], and TG [11]. About 20 identified genetic polymorphisms, including both thyroid-specific genes and those regulating the autoimmune response were already investigated.…”
Section: Introductionmentioning
confidence: 98%
“…The first group is those genes common to many autoimmune diseases and involving immune regulatory and response genes. These include HLA-DR3 (7,8), CTLA4 (9,10), PTPN22 (11,12), CD40 (13,14), IL2RA (CD25) (15,16), FCRL3 (17,18), and the IL23R (19). The second group includes genes that are specific to the thyroid gland: the TSHR (20-24) and thyroglobulin (TG) (25,26).…”
Section: Introductionmentioning
confidence: 99%